'Alles strijdt, wat naar vrijheid haakt.' Theorievorming over de staking in de Belgische politiek, 1884-1914 - J. Deferme (BMGN: Low Countries Historical Review, 2002)
Struggling for freedom. Social theory on strike actions in Belgian politics, 1884-1914 In nineteenth century workers' songs, the strike was presented as a heroic struggle for freedom. At first sight, the arguments in political debates more or less followed this same line of thought, in that several 'socially progressive' politicians defended strike actions using the argument of 'right of association'; a right that the working class also claimed in their struggle for emancipation. Yet the dominant political attitude towards the social question during those years was inspired by social control rather than emancipation. Therefore, when petitioners had to arouse parliamentary sympathy for strikes, they smartly abandoned the discourse linked to the struggle for freedom, and instead chose to present strikes not as heroic, voluntary actions, but rather as something inevitable; a 'force majeure'. This presentation was a radical departure from the traditional liberal values of individual responsibility, and was, instead, inspired by a very modern sociological discourse. This even went so far as to question the ultimate roots of the legal system itself, viz. the basic principles of civil law.